The Measuring Health Clinic Success: A Balanced Scorecard Approach to Improve Performance and Service - Dewi Agustya Ningrum; Eka Maulid Diana (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
A health clinic is a primary healthcare facility (PHF) that provides health services with organized professional staff and comprehensive medical facilities to deliver continuous care, including diagnosis and treatment of patients' illnesses. As a service company in the healthcare sector, this clinic plays an important role in providing medical services to the community. This study aims to evaluate the performance of a Health Clinic using the Balanced Scorecard (BSC) approach. Within the BSC framework, there are four main perspectives used to assess performance: 1) Financial Perspective; 2) Customer Perspective; 3) Internal Business Processes Perspective; and 4) Growth and Learning Perspective. The type of research conducted is descriptive qualitative, with primary and secondary data sources collected from 2021 to 2023. The use of BSC in this study is expected to provide knowledge management, skills, and systems that support the development of employee creativity and management, thereby increasing efficiency, consistency, and timeliness in service delivery. As a result, the services provided can offer benefits and improve customer satisfaction, ultimately contributing to increased company profits. The research findings indicate that the clinic's performance across the four perspectives shows varied results: the financial perspective, with indicators such as ROI and Debt to Asset Ratio, shows suboptimal results; the customer perspective, with customer acquisition indicators, shows good results, but customer satisfaction levels are still lacking; the internal business process perspective indicates that outpatient waiting times are still insufficient, while emergency department waiting times are rated good; and the growth and learning perspective shows positive results in employee retention and productivity.